Process for optimizing grain size grade difference of large-size nickel-based superalloy bar

By studying the thermal deformation resistance of elements in GH4169 high-temperature alloy rods, designing a reasonable component control range, and adopting four-stage diffusion annealing and two-pull + two-upset deformation technology, the large grain size difference of large-sized rods is solved. The problem is to improve the uniformity of bar grains and performance consistency, while reducing production costs and equipment requirements.

CN119411047APending Publication Date: 2025-02-11JIANGSU LONGDA SUPERALLOY MATERIAL CO LTD

Patent Information

Application Number
CN202411719262.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the grain size difference of large-sized GH4169 high-temperature alloy rods, especially in large-sized rods with diameters ≥350mm, especially in diameters ≥400mm, the grain size difference is large, resulting in large performance differences.

Method used

通过研究元素对GH4169的热变形抗力,设计合理的成分控制范围,降低锻造热变形抗力,并采用四段式扩散退火和两拔+两镦变形工艺,结合锻前、锻后低温热处理,优化锻造环境温度,控制棒材的晶粒度级差。

Benefits of technology

It effectively reduces the grain size difference of large-size GH4169 rods, ensures grain uniformity of rods, improves performance consistency, and reduces production costs and equipment requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411047A_ABST
    Figure CN119411047A_ABST
Patent Text Reader

Abstract

The invention provides a process for optimizing the grain size grade difference of a large-size nickel-based superalloy bar, and belongs to the technical field of nickel-based superalloy bar manufacturing. The process comprises the following steps that S1, raw materials are weighed and smelted to obtain an electroslag ingot; s2, uniform diffusion annealing is carried out; s3, heating before forging to obtain a forging stock; s4, the forging stock is subjected to two times of drawing-out and two times of upsetting treatment, and a semi-finished product is obtained; and S5, the semi-finished product is continuously drawn out, and the bar is obtained. Through the integral design of the whole process scheme such as component design, four-section type diffusion annealing and setting of the forging temperature and the environment temperature, the thermal deformation resistance during forging is greatly reduced, center grains are refined, the grain size grade difference from the edge to the core of the GH4169 bar is controlled within the 1.5 grade, and the process is feasible, low in cost and suitable for large-scale production. The problem that the grain size grade difference of the nickel-based superalloy bar with the diameter larger than or equal to 350 mm is large is solved for the first time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nickel-based high-temperature alloy rod manufacturing, and in particular to a process for optimizing the grain size difference of large-size nickel-based high-temperature alloy rods. Background Art

[0002] The most representative and most in-demand alloy grade of high-temperature alloys is GH4169. GH4169 high-temperature alloy is called 718 alloy abroad. It is regarded as the mainstay of high-temperature alloys in Europe and the United States and is known as a universal high-temperature alloy. New fighter jets and large aircraft at home and abroad mainly use GH4169 high-temperature alloy as the heart component of the engine - turbine disc. At present, my country imports about 10,000 tons of deformable high-temperature alloys from abroad each year, of which 80% of GH4169 alloy is imported, which has formed a clear constraint on my country's development of a new generation of aircraft, aero engines, gas turbines, etc.

[0003] my country has a certain level of technology and production scale in GH4169 high-temperature alloy. However, for large-size bars with a diameter of ≥350mm, especially those with a diameter of ≥400mm, there is a large difference in grain size between the outer circle, R1 / 2 and the center, resulting in large performance differences. The technical root cause is the four combined factors of small deformation per pass, large resistance to thermal deformation of the material, severe heat loss in the outer circle and grain growth due to temperature rise in the center.

[0004] Patent application number CN 109371344 A discloses a forging process for GH4169 alloy bars. By controlling forging parameters, bars with uniform grain size and reduced grain size difference can be obtained. However, according to the deformation process in its embodiment, it can be seen that: (1) the diameter of the finished bar does not exceed 300 mm; and large-sized bars with a diameter ≥ 350 mm, especially with a diameter ≥ 400 mm, are the real bottleneck for the uniform grain size of GH4169; (2) the cost of the triple melting process is higher; (3) the deformation process adopts three-upsetting and three-drawing + radial forging, among which the three-upsetting and three-drawing processes are more common, and each additional process means increased cost and reduced production efficiency; the radial forging process has extremely high requirements on equipment. At present, the radial forging machines used in China are basically imported and extremely expensive.

[0005] The patent application with patent application number CN 110449541 A discloses a manufacturing process for GH4169 high-temperature alloy free forging bar blanks. By controlling the forging parameters, the grain size difference can be controlled within one level, but the diameter of the finished bar is 250mm to 350mm; and large-sized bars with a diameter ≥350mm, especially with a diameter ≥400mm, are the real bottleneck for the uniform grain size of GH4169 because the deformation per pass is small. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the prior art, provide a process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars, and control the grain size difference of large-sized GH4169 bars.

[0007] The technical solution adopted by the present invention is: A process for optimizing the grain size difference of a large-size nickel-based high-temperature alloy rod, wherein: the alloy composition of the rod, by mass percentage, includes: Ni 53.0~55.0 wt%, Nb 4.95~5.20 wt%, Ti 0.75~1.00 wt%, Al 0.30~0.50 wt%, Mo 2.80~3.00 wt%, C 0.015~0.060 wt%, Cr 17.00~21.00 wt%, Fe balance, the total of which is 100%; By studying the effect of elements on the thermal deformation resistance of GH4169, a reasonable composition control range was designed to reduce the thermal deformation resistance during forging, provide composition and organizational preparation for increasing the subsequent forging deformation of large-size GH4169 bars, and improve the grain size difference of the bars.

[0008] The process includes the following steps: Step S1. Weighing C, Ni, Cr, Mo, Al, Ti, Nb, and Fe block raw materials according to the alloy composition of the rod, and smelting them by double smelting to obtain an electroslag ingot; Step S2. performing homogenization diffusion annealing on the electroslag ingot; Step S3. heating the annealed electroslag ingot before forging to obtain a forging blank; Step S4. The forging blank after pre-forging heating is subjected to two stretching and two upsetting treatments to obtain a semi-finished bar; Step S5: Continuously stretch the semi-finished rod to the finished product specifications to obtain a rod.

[0009] Preferably, the process for optimizing the grain size difference of large-size nickel-based high-temperature alloy rods, wherein: the homogenization diffusion annealing in step S2 is specifically: the electroslag ingot is kept at 730-750°C for 7-9h, then the temperature is increased to 1155-1165°C at a rate of 50-90°C / h and kept for 23-27h, then the temperature is increased to 1185-1195°C at a rate of 50-90°C / h and kept for 110-115h, then the temperature is decreased to 1080-1090°C at a rate of 45-55°C / h and kept for 3-5h, and finally taken out of the furnace and air-cooled.

[0010] The scientific process of segmented high-temperature annealing is adopted to avoid the solid-liquid two-phase produced by Laves initial melting in large-sized nickel-based high-temperature alloy bars, while eliminating the segregation of Nb elements, solving the biggest problem of Nb segregation in the alloy.

[0011] Preferably, the process for optimizing the grain size difference of large-size nickel-based high-temperature alloy rods, wherein: the pre-forging heating in step S3 is specifically: keeping the annealed electroslag ingot at 735-745°C for 5-6 hours, then heating it to 1075-1085°C at a rate of 50-90°C / h, and keeping it for 6-8 hours.

[0012] Preferably, the process for optimizing the grain size difference of large-size nickel-based high-temperature alloy rods, wherein: the deformation amount of drawing in step S4 is 36%~40%, and the deformation amount of upsetting is 36%~40%; heat treatment is performed after each drawing or upsetting, the heat treatment temperature is 1075~1095℃, and the heat treatment time is 0.8~1.2h.

[0013] The two-drawing + two-upsetting deformation process is adopted. Compared with the traditional process of upsetting first and then drawing, this method can completely break the molten cast crystals to form better and more uniform equiaxed crystals, which provides a guarantee for the uniformity of the finished grains.

[0014] Preferably, the process for optimizing the grain size difference of large-size nickel-based high-temperature alloy rods, wherein: the amount of drawing deformation in step S5 is 36%~40%; heating is performed after each drawing, the temperature of the last heating is 975~995°C, and the holding time is 0.5~1h; the temperature of heating after other drawing times is 1000~1020°C, and the holding time is 0.8~1.2h.

[0015] Preferably, the process for optimizing the grain size difference of large-size nickel-based high-temperature alloy bars, wherein: the time between the forging blank being taken out of the furnace after heat treatment in step S4 and the start of the next drawing or upsetting is ≤40S, and the ambient temperature during the two drawing and two upsetting treatments is 30-38°C.

[0016] By studying the mechanism of grain growth during the forging process, the present invention sets a scientific forging environment temperature. This parameter is generally ignored in the industry because it is difficult to detect, which reduces the temperature drop rate on the surface of the rod by more than half, prolongs the effective forging time, makes the surface of the rod deform fully, and refines the grains.

[0017] Preferably, in the process for optimizing the grain size difference of large-size nickel-based high-temperature alloy rods, the time between the semi-finished product being taken out of the furnace after heating in step S5 and the start of the next drawing is ≤40S, and the ambient temperature during the continuous drawing process is 30-38°C.

[0018] Advantages of the present invention: (1) The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars of the present invention designs a reasonable composition control range by studying the effect of elements on the thermal deformation resistance of GH4169, reduces the forging thermal deformation resistance, increases the forging deformation of large-sized GH4169 bars, and improves the grain size difference of the bars.

[0019] (2) The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy rods of the present invention adopts a four-stage diffusion annealing process, which avoids the solid-liquid two-phase produced by Laves initial melting and eliminates the segregation of Nb elements, thereby solving the biggest problem of Nb segregation in the alloy, thereby increasing the subsequent forging deformation of large-sized GH4169 rods and improving the grain size difference of the rods.

[0020] (3) By studying the relationship between the surface temperature drop and the ambient temperature of the GH4169 bar after heat treatment, low-temperature heat treatment before and after forging was adopted, combined with a reasonable design of the ambient temperature, which reduced the surface temperature drop rate of the bar by more than half, extended the effective forging time, made the surface deformation of the bar sufficient, and refined the grains; at the same time, the low heat treatment setting made the grains in the center of the bar grow slowly, and improved the grain size difference between the center and the outer circle of the bar.

[0021] (4) Through composition design, four-stage diffusion annealing, and the setting of forging temperature and ambient temperature, the thermal deformation resistance during forging is greatly reduced. The integrated design of the overall process scheme enables the use of large deformation forging process, refinement of central grains, and control of the grain size difference from the edge to the center of large-size GH4169 bars with a diameter of ≥350 mm within 1.5 levels.

[0022] (5) The present invention adopts a two-drawing + two-upsetting deformation process. Compared with the traditional process of upsetting first and then drawing, this method allows the molten cast crystal to be completely broken to form better and more uniform equiaxed crystals, thus providing a guarantee for the uniformity of the finished grains. At the same time, compared with the radial forging machine, this process has low equipment requirements and low production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the grain size diagram of the outer circle of the Φ350mm rod prepared in Example 1.

[0024] Figure 2 This is the grain size diagram of the Φ350mm rod R1 / 2 prepared in Example 1.

[0025] Figure 3 This is the grain size diagram at the center of the Φ350mm rod prepared in Example 1.

[0026] Figure 4 This is the grain size diagram of the outer circle of the Φ400mm rod prepared in Example 2.

[0027] Figure 5 This is the grain size diagram of the Φ400mm rod R1 / 2 prepared in Example 2.

[0028] Figure 6 This is the grain size diagram at the center of the Φ400mm rod prepared in Example 2.

[0029] Figure 7 This is the grain size diagram of the outer circle of the Φ450mm rod prepared in Example 3.

[0030] Figure 8 This is the grain size diagram of the Φ450mm rod R1 / 2 prepared in Example 3.

[0031] Fig. 9 This is the grain size diagram at the center of the Φ450mm rod prepared in Example 3. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments.

[0033] Example 1 A process for refining the grain size of a rod, wherein the alloy composition of the rod, by mass percentage, comprises: Ni 53.46 wt%, Nb 5.09 wt%, Ti 0.78 wt%, Al 0.36 wt%, Mo 2.85 wt%, C 0.029 wt%, Cr 18.92 wt%, Fe balance, the total of which is 100%; The process includes the following steps: Step S1. Weigh the raw materials according to the alloy composition of the rod and use vacuum induction + electroslag remelting to obtain a Φ508 electroslag ingot; wherein the casting temperature of the vacuum induction melting using the vacuum induction furnace is 1472°C, and the melting rate of the electroslag remelting using the electroslag remelting furnace is 4.9kg / min; Step S2. The Φ508 electroslag ingot is subjected to homogenization diffusion annealing. The homogenization diffusion annealing is specifically as follows: the electroslag ingot is kept at 730°C for 7h, then heated to 1155°C at a rate of 50°C / h for 23h, then heated to 1185°C at a rate of 50°C / h for 110h, then cooled to 1080°C at a rate of 45°C / h for 3h, and finally removed from the furnace and air-cooled; Step S3. The annealed electroslag ingot is heated before forging. Specifically, the annealed electroslag ingot is kept at 735°C for 5 hours, then heated to 1075°C at a rate of 50°C / h, and kept for 6 hours to obtain a forging blank; Step S4. The forging blank after pre-forging heating is subjected to two stretching and two upsetting treatments, the stretching deformation is 36%, and the upsetting deformation is 36%; heat treatment is performed after each stretching or upsetting, the heat treatment temperature is 1075°C, the heat treatment time is 0.8h, the time between the forging blank being taken out of the furnace after the heat treatment and the start of the next stretching or upsetting is 32s on average, specifically 28-35s, the ambient temperature during the two stretching and two upsetting treatments is 32°C, and a semi-finished bar is obtained; Step S5. The semi-finished bar is continuously drawn to a finished product specification of Φ350mm, with an average drawing deformation of 38%, specifically 36%~40%; heating is performed after each drawing, the temperature of the last heating is 975℃, and the insulation time is 0.5h; the heating temperature after other drawing is 1000℃, and the insulation time is 0.8h. The time between the semi-finished product being taken out of the furnace after heating and the start of the next drawing is an average of 34s, specifically in the range of 32~35s. The ambient temperature during the continuous drawing process is 31℃, and a Φ350mm bar is obtained.

[0034] Figure 1 This is the outer circle grain size diagram of the Φ350mm rod prepared in Example 1, with a grain size of 6.5; Figure 2 This is the grain size diagram of Φ350mm bar R1 / 2, grain size 6.0, Figure 3 This is a grain size diagram of the center of a Φ350mm rod, with a grain size of 6.0. The Φ350mm large-size rod product of GH4169 prepared in this embodiment has a grain size difference of 0.5 from the outer circle to the center, and the grains are uniform.

[0035] Example 2 A process for refining the grain size of a rod, wherein the alloy composition of the rod, by mass percentage, comprises: Ni 54.61 wt%, Nb 5.09 wt%, Ti 0.87 wt%, Al 0.39 wt%, Mo 2.92 wt%, C 0.042 wt%, Cr 18.88 wt%, Fe balance, the total of which is 100%; The process includes the following steps: Step S1. Weigh the raw materials according to the alloy composition of the rod and use vacuum induction + electroslag remelting to obtain a Φ508 electroslag ingot; wherein the casting temperature of the vacuum induction melting using the vacuum induction furnace is 1473°C, and the melting rate of the electroslag remelting using the electroslag remelting furnace is 5.2kg / min; Step S2. The electroslag ingot is subjected to homogenization diffusion annealing. The homogenization diffusion annealing is specifically as follows: the electroslag ingot is kept at 740°C for 8 hours, then heated to 1160°C at a rate of 70°C / h for 25 hours, then heated to 1189°C at a rate of 70°C / h for 110 hours, then cooled to 1085°C at a rate of 50°C / h for 4 hours, and finally removed from the furnace and air-cooled; Step S3. The annealed electroslag ingot is heated before forging. Specifically, the annealed electroslag ingot is kept at 740°C for 5.5 hours, and then heated to 1080°C at a rate of 70°C / h, and kept for 7 hours to obtain a forging blank; Step S4. The forging blank after pre-forging heating is subjected to two drawing and two upsetting treatments, the drawing deformation is 38%, and the upsetting deformation is 38%; heat treatment is performed after each drawing or upsetting, the heat treatment temperature is 1080°C, the heat treatment time is 1h, the time between the forging blank being taken out of the furnace after the heat treatment and the start of the next drawing or upsetting is 30s on average, specifically in the range of 25-33s, the ambient temperature during the two drawing and two upsetting treatments is 35°C, and a semi-finished bar is obtained; Step S5. The semi-finished bar is continuously drawn to a finished product specification of Φ400mm, with an average drawing deformation of 38%, specifically 37%~39.5%; heating is performed after each drawing, the temperature of the last heating is 985°C, and the insulation time is 0.8h; the heating temperature after other drawing is 1010°C, and the insulation time is 1h. The time between the semi-finished product being taken out of the furnace after heating and the start of the next drawing is an average of 35s, specifically in the range of 32~37s. The ambient temperature during the continuous drawing process is 33°C, and the bar is obtained.

[0036] Figure 4 This is the outer circle grain size diagram of the Φ400mm rod prepared in Example 2, with a grain size of 7.5; Figure 5 This is the grain size diagram of Φ400mm bar R1 / 2, grain size 7.0, Figure 6 This is the grain size diagram of the center of the Φ400mm rod, with a grain size of 6.5. The Φ400mm large-size rod product of GH4169 prepared in this embodiment has a grain size difference of 1 from the outer circle to the center, and the grains are uniform.

[0037] Example 3 A process for refining the grain size of a rod, wherein the alloy composition of the rod, by mass percentage, comprises: Ni 54.89 wt%, Nb 5.11 wt%, Ti 0.82 wt%, Al 0.46 wt%, Mo 2.94 wt%, C 0.051 wt%, Cr 20.03 wt%, Fe balance, the total of which is 100%; The process includes the following steps: Step S1. Weigh the raw materials according to the alloy composition of the rod and use vacuum induction + electroslag remelting to obtain a Φ508 electroslag ingot; wherein the casting temperature of the vacuum induction melting using the vacuum induction furnace is 1482°C, and the melting rate of the electroslag remelting using the electroslag remelting furnace is 6.1kg / min; Step S2. The electroslag ingot is subjected to homogenization diffusion annealing. Specifically, the electroslag ingot is kept at 750°C for 9 hours, then heated to 1165°C at a rate of 90°C / h for 27 hours, then heated to 1195°C at a rate of 90°C / h for 115 hours, then cooled to 1090°C at a rate of 55°C / h for 5 hours, and finally taken out of the furnace for air cooling; Step S3. The annealed electroslag ingot is heated before forging. Specifically, the annealed electroslag ingot is kept at 745°C for 6 hours, and then heated to 1085°C at a rate of 90°C / h, and kept for 8 hours to obtain a forging blank; Step S4. The forging blank after pre-forging heating is subjected to two stretching and two upsetting treatments, the stretching deformation is 40%, and the upsetting deformation is 40%; heat treatment is performed after each stretching or upsetting, the heat treatment temperature is 1095°C, the heat treatment time is 1.2h, the time between the forging blank being taken out of the furnace after the heat treatment and the start of the next stretching or upsetting is 27s on average, specifically in the range of 25-28s, the ambient temperature during the two stretching and two upsetting treatments is 37°C, and a semi-finished bar is obtained; Step S5. The semi-finished bar is continuously drawn to a finished product specification of Φ450mm, with an average drawing deformation of 39.8%, specifically 39.5%~40%; heating is performed after each drawing, the temperature of the last heating is 995°C, and the insulation time is 1h; the heating temperature after other drawing is 1020°C, and the insulation time is 1.2h. The time between the semi-finished product being taken out of the furnace after heating and the start of the next drawing is an average of 33 seconds, specifically in the range of 32~35s. The ambient temperature during the continuous drawing process is 33°C to obtain a bar.

[0038] Figure 7 This is the grain size diagram of the outer circle of the Φ450mm rod prepared in Example 3, with a grain size of 7.5; Figure 8 This is the grain size diagram of Φ450mm bar R1 / 2, grain size 6.5, Fig. 9 This is a grain size diagram of the center of a Φ450mm rod, with a grain size of grade 6. The Φ450mm large-size rod product of GH4169 prepared in this embodiment has a grain size difference of 1.5 from the outer circle to the center, and the grains are uniform.

[0039] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A process for optimizing the grain size difference of large-size nickel-based high-temperature alloy bars, characterized in that: The alloy composition of the rod, by mass percentage, includes: Ni 53.0~55.0 wt%, Nb 4.95~5.20 wt%, Ti 0.75~1.00 wt%, Al0.30~0.50 wt%, Mo 2.80~3.00 wt%, C 0.015~0.060 wt%, Cr 17.00~21.00 wt%, Fe balance, the above total is 100%; The process includes the following steps: Step S1. Weigh C, Ni, Cr, Mo, Al, Ti, Nb, and Fe block raw materials according to the alloy composition of the rod, and smelt them by double smelting to obtain an electroslag ingot; Step S2. performing homogenization diffusion annealing on the electroslag ingot; Step S3. heating the annealed electroslag ingot before forging to obtain a forging blank; Step S4. The forging blank after heating before forging is subjected to two stretching and two upsetting treatments to obtain a semi-finished product; Step S5: Continuously stretch the semi-finished product to the finished product specification to obtain a rod.

2. The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars according to claim 1 is characterized in that: The homogenization diffusion annealing in step S2 is specifically as follows: the electroslag ingot is kept at 730-750°C for 7-9h, then the temperature is increased to 1155-1165°C at a rate of 50-90°C / h and kept for 23-27h, then the temperature is increased to 1185-1195°C at a rate of 50-90°C / h and kept for 110-115h, then the temperature is decreased to 1080-1090°C at a rate of 45-55°C / h and kept for 3-5h, and finally taken out of the furnace and air-cooled.

3. The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars according to claim 1 is characterized in that: The heating before forging in step S3 is specifically as follows: the annealed electroslag ingot is kept at 735-745°C for 5-6 hours, then heated to 1075-1085°C at a rate of 50-90°C / h, and kept at this temperature for 6-8 hours.

4. The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars according to claim 1 is characterized in that: In step S4, the deformation amount of the drawing is 36%-40%, and the deformation amount of the upsetting is 36%-40%; heat treatment is performed after each drawing or upsetting, the heat treatment temperature is 1075-1095°C, and the heat treatment time is 0.8-1.2h.

5. The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars according to claim 1 is characterized in that: The deformation amount of the drawing in step S5 is 36%~40%; heating is performed after each drawing, the temperature of the last heating is 975~995℃, and the insulation time is 0.5~1h; the heating temperature after other drawing is 1000~1020℃, and the insulation time is 0.8~1.2h.

6. The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars according to claim 4 is characterized in that: In step S4, the time from when the forging blank is taken out of the furnace after heat treatment to when the next drawing or upsetting begins is ≤40S, and the ambient temperature during the two drawing and two upsetting treatments is 30-38°C.

7. The process for optimizing the grain size difference of large-sized nickel-based high-temperature alloy bars according to claim 5 is characterized in that: The time between the semi-finished product being taken out of the furnace after heating in step S5 and the start of the next stretching is ≤40S, and the ambient temperature during the continuous stretching process is 30-38°C.

Citation Information

Patent Citations

  • Forging process of GH4169 alloy bar

    CN109371344A

  • GH4169 high-temperature alloy free-forged bar billet and preparation method thereof

    CN110449541A

Cited By

  • Super-large ingot type high-temperature alloy forging material and preparation method thereof

    CN120967271A

  • Method for controlling structure uniformity of large-size ultralow-expansion alloy bar

    CN121374029A